2021
DOI: 10.1111/wrr.12913
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIR503HG promotes hypertrophic scar progression via miR‐143‐3p‐mediated Smad3 expression

Abstract: Hypertrophic scars (HSs) form due to unchecked proliferation of fibrous tissue after an injury to the skin. Recently, lncRNA MIR503HG was shown to be involved in HS. However, the mechanism by which MIR503HG affects the formation and progression of HS still needs further study. qRT-PCR was applied to examine the levels of MIR503HG and miR-143-3p in HS tissues and human hypertrophic scar fibroblasts (hHSFs). The relationships of MIR503HG, miR-143-3p and Smad3 were explored with a dual-luciferase reporter assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Wei et al found that miR-143-3p was downregulated in HS compared with normal skin tissue, and the overexpression of miR-143-3p inhibited the proliferation and invasion of HSF and promoted its apoptosis. They also confirmed that miR-143-3p played the above role by directly targeting Smad3 [20].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Wei et al found that miR-143-3p was downregulated in HS compared with normal skin tissue, and the overexpression of miR-143-3p inhibited the proliferation and invasion of HSF and promoted its apoptosis. They also confirmed that miR-143-3p played the above role by directly targeting Smad3 [20].…”
Section: Discussionsupporting
confidence: 52%
“…Wei et al found that miR-143-3p was downregulated in HS compared with normal skin tissue, and the overexpression of miR-143-3p inhibited the proliferation and invasion of HSF and promoted its apoptosis. They also confirmed that miR-143-3p played the above role by directly targeting Smad3 [ 20 ]. Besides, miR-92a-3p [ 21 ] was also involved in the development of various fibrotic diseases, but the correlation with keloid has not been reported.…”
Section: Discussionmentioning
confidence: 70%
“…Activation of AMPK/Sirt1 pathway is reported to restore impaired autophagy and inhibited inflammation reaction and apoptosis in acute pancreatitis, acute kidney injury, diabetic retinopathy and age-related mitochondrial dysfunction. 39 42 However, the role of AMPK/Sirt1-mediated autophagy is not clearly investigated in II/R. In this study, we found that a decrease in p-AMPK/AMPK and Sirt1 protein expression in II/R rats and CA pretreatment promoted AMPK phosphorylation and Sirt1 expression.…”
Section: Discussionmentioning
confidence: 64%
“…Another candidate lncRNA identified in our study, MIR503HG , has been previously described to be deregulated in tongue squamous cell carcinoma [ 38 ]. Of note, MIR503HG has been also associated with the promotion of pathophysiological processes mediated by dermal fibroblasts, including hypertrophic scar progression [ 39 ], and skin fibrosis, via interaction with TGFB/SMAD signaling [ 40 ].…”
Section: Discussionmentioning
confidence: 99%